Patterning of Poly (vinylidene fluoride) thin films using soft Lithography: Structural characterization - M. S. Ravisankar (International Journal of Advanced Science and Technology, 2020)
This paper focuses on the optimization of the nano-patterns of Poly (vinylidene fluoride) (PVDF) thin films on Glass  substrates using soft  Imprint Lithography. The compact disc (CD) aluminum layer was used as a master to transfer  the nano-patterns. Tetrahydrofuran(THF) solvent is exploited to fabricate the thin films. Imprint lithography is employed to transfer the nano-patterns onto the PVDF thin films systematically under optimized temperature and pressure. Atomic Force Microscopy (AFM) has been used to analyze the nano-pattern transfer and its surface smoothness patterned  and unpaternted films. Furthermore, Raman spectroscopy of the patterned PVDF thin films has been used for discussing the structural deviations and crystanility from the un-patterned PVDF thin films.